Decreased Plasma Aβ in Hyperlipidemic APPSL Transgenic Mice Is Associated with BBB Dysfunction - Löffler, Tina; Flunkert, Stefanie; Temmel, Magdalena; Hutter-Paier, Birgit (Frontiers in Neuroscience, 2016)
Besides the continued focus on Aβ and Tau in Alzheimer’s disease (AD), it is increasingly evident that other pathologic characteristics, such as vascular alterations or inflammation, are associated with AD. Whether these changes are an initial cause for the onset of AD or occur as a result of the disease in late stages is still under debate. In the present study, the impact of the high-fat diet (HFD) induced vascular risk factor hyperlipidemia on Aβ levels and clearance as well as cerebral vasculature and blood-brain barrier (BBB) integrity was examined in mice. For this purpose, human APP transgenic (APPSL) and wildtype (WT) mice were fed a HFD for 12 weeks. Plasma and tissues were subsequently investigated for Aβ distribution and concentrations of several vascular markers. Decreased plasma Aβ together with increased levels of insoluble Aβ and amyloid plaques in the brains of HFD fed APPSL mice point towards impaired Aβ clearance due to HFD. Additionally, HFD induced manifold alterations in the cerebral vasculature and BBB integrity exclusively in human APP overexpressing mice but not in wildtype mice. Therefore, HFD appears to enhance Aβ dependent vascular/BBB dysfunction in combination with an increased proportion of cerebral to plasma Aβ in APPSL mice.